Prediction of spontaneous eruption of palatally displaced canine based on variables measurements in panoramic radiograph: A systematic review - Neeteesh K. Shukla; Vipul K. Sharma; T.P. Chaturvedi; Ajit V. Parihar; Vinay K. Chugh (Elsevier, 2021)
Objective: This systematic review was aimed to find out possible predictive variables measured on panoramic radiographs to predict spontaneous eruption of palatally displaced canine (PDC) after interceptive extraction in late mixed dentition. Materials and methods: Electronic database searches were performed in MEDLINE, Cochrane's CENTRAL, Scopus, and in other sources up to June 2020. Randomized and nonrandomized controlled trials, and pre-post prospective studies without control groups were considered for review. Study selection, data extraction, risk of bias assessment (by RoB 2.0, ROBINS-I, and NHLBI score), and the certainty of evidence evaluation (GRADE approach) were performed during reviewing process. Only qualitative analyses of included literature were done due to presence of between study heterogeneity. Results: Out of 970 retrieved records, 3 controlled trials and 3 prospective before and after studies without control fulfilled the eligibility criteria and were included in the review. Studies were assessed at low risk to high risk of bias. Overall certainty was moderate to very low. Results shows that PDCs in distal sectors, lower alpha angle, younger subjects, PDCs with less advanced developed root were significantly benefited from interceptive extraction. However, Vertical distance had insignificant roll on eruption prediction. Conclusions: Interceptive extraction at younger age, mesial canine crown position (sectors), and mesial inclination of PDC (alpha angulation) are the most important variables predicting the spontaneous eruption of palatally displaced canine. Findings of this review can be utilized to make evidence-based decisions for managing PDCs with diverse sectors and mesial inclinations. However, well designed clinical trials are recommended to strengthen the evidence.